Assessment of resident doctors’ knowledge levels regarding radiation doses during routine radiological investigations - Selin Doğan Jamil; Amirreza Teymourfamian Asl; Badiozzaman Hosseinpour; Nimet Emel Lüleci (New Zealand Medical Student Journal)
This descriptive study, conducted from April to June 2023, surveyed 235 resident doctors at a state university hospital in Istanbul, Türkiye to assess their knowledge of the ionising radiation dose received by patients during various radiological imaging procedures. Participants, selected through a non-random convenience sampling method, compared radiation exposure from commonly used radiological exams to that of a standard chest X-ray. Data were analysed using the Chi-Square Test and Fisher’s Exact Test. Among 235 (resident doctors surveyed, radiology, and related specialty (nuclear medicine and radiation oncology) residents demonstrated superior accuracy in estimating radiation doses for various radiological tests compared to their counterparts in other departments. Notably, 98.3% of participants accurately estimated pelvic magnetic resonance imaging doses and 99.1% for ultrasound, with no significant differences across departments. Overall, factors such as age, gender, graduation year, and general practice experience did not significantly affect the accuracy of dose estimations.